ChemInform Abstract: The Development of Zn—Ce Hybrid Redox Flow Batteries for Energy Storage and Their Continuing Challenges. Issue 14 (April 2015) - Walsh, Frank C.; Ponce de Leon, Carlos; Berlouis, Len; Nikiforidis, George; Arenas‐Martinez, Luis F.; Hodgson, David; Hall, David
Abstract: Review: [100 refs.]